Simple and Cost-Effective Design of a THz-Metamaterial-Based Hybrid Sensor on a Single Substrate - Uddipan Nath; Sagnik Banerjee; Carlo Santini; Rocco Citroni; Fabio Mangini; Fabrizio Frezza (Sensors, 2025)
This study presents a cost-effective Hybrid Metamaterial Absorber (HMA) featuring a simple circular-patterned cylindrical design, comprising an indium antimonide (InSb) resonator on a thin copper sheet. Through numerical simulations, we demonstrate that the structure exhibits temperature-tunable properties and refractive index sensitivity. At 300 K (refractive index = 1), a peak absorption of 99.94% is achieved at 1.797 THz. Efficient operation is observed across a 40 K temperature range and a refractive index spectrum of 1.00–1.05, relevant for thermal imaging and spatial bio-sensing. The simulated temperature sensing sensitivity is 13.07 GHz/K, and the refractive index sensitivity is 1146 GHz/RIU. Parametric analyses reveal tunable absorption through adjustments of the InSb resonator design parameters. Owing to its high efficiency and sensitivity demonstrated in simulations, this HMA shows promise for sensing applications in biotechnology, semiconductor fabrication, and energy harvesting.